Advancing SDGs 4, 5, and 16 through Islamic Cultural Conscientization in Indonesian Biographical Cinema: A Freirean–Peircean Analysis Using the CCSP Model - Frikho Fernando Polii; Suyatno suyatno; Darni Darni (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2027)
Objective: How Islamic cultural conscientization is constructed in Indonesian biographical films through pedagogical and semiotic mechanisms. Method: The research adopts a qualitative interpretive-critical design grounded in Freirean conscientization, Peircean semiotics, and postcolonial cultural theory. Data were collected through repeated film observation, time-coded scene documentation, and semiotic transcription of selected cinematic units. Results: The findings indicate that Islamic literacy operates as a cognitive framework for understanding structural inequalities such as colonialism, patriarchy, and feudalism. Affective representations of suffering and moral tension construct empathy as an ethical learning process. Transformative praxis emerges through educational initiatives, organizational leadership, and cultural resistance embedded in cinematic narratives. Novelty: The study develops the Cultural Conscientization Semiotic Pedagogy (CCSP) Model, positioning Indonesian biographical cinema as a medium of Islamic cultural conscientization that integrates cognition, emotion, and social action within SDGsoriented educational discourse.